2017
DOI: 10.1002/anie.201701185
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Target Residence Time: Type I Inhibitors for p38α MAP Kinase with Improved Binding Kinetics through Direct Interaction with the R‐Spine

Abstract: Skepinone-L was recently reported to be a p38α MAP kinase inhibitor with high potency and excellent selectivity in vitro and in vivo. However, this class of compounds still act as fully ATP-competitive Type I binders which, furthermore, suffer from short residence times at the enzyme. We herein describe a further development with the first Type I1/2 binders for p38α MAP kinase. Type I1/2 inhibitors interfere with the R-spine, inducing a glycine flip and occupying both hydrophobic regions I and II. This design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…More recently, novel p38 MAPK inhibitors including 36 and 37 have been reported to target both active and inactive states of p38 MAPK for the increased target residence time. They are made up of glycine flip-inducing moieties and binders interacting with the R-spine, which make the compounds have excellent kinase selectivities, significantly potent activities on the enzyme level and in the cell based assay ( Figure 11 ) [ 162 ]. The use of potent and selective p38 MAPK inhibitors would further reveal their potential for the treatment of AD and reduced off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, novel p38 MAPK inhibitors including 36 and 37 have been reported to target both active and inactive states of p38 MAPK for the increased target residence time. They are made up of glycine flip-inducing moieties and binders interacting with the R-spine, which make the compounds have excellent kinase selectivities, significantly potent activities on the enzyme level and in the cell based assay ( Figure 11 ) [ 162 ]. The use of potent and selective p38 MAPK inhibitors would further reveal their potential for the treatment of AD and reduced off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…34 Other examples include antagonists of the muscarinic M3 receptor, 35 antagonists of the chemoattractant receptor-homologous molecule CRTh2/DP2, 36 and inhibitors of p38α MAP kinase. 37 The second major misconception is that if a compound has similar IC 50 values for two different proteins, the drug-target and an off-target protein associated with unwanted side-effects, then the compound has no selectivity. Indeed, the compound has no thermodynamic selectivity, but if the k on and k off values differ between the two targets, it can still have kinetic selectivity.…”
Section: The Thermodynamics and Kinetics Of Drug–target Interactionsmentioning
confidence: 99%
“…In this context, we have previously reported that among p38α MAPK inhibitors, the type I½ inhibitor regulatory-spine (R-spine) interaction is important for increased target residence time 26 28 . However, these type I½ inhibitors have not been studied by the means of long timescale simulations to date and a precise understanding of the underlying mechanisms is still incomplete.…”
Section: Introductionmentioning
confidence: 99%